Isolation and characterization of entomopathogenic fungi from selected recreational forests in the Kinta region, Perak - Chong, Zheng Yang (2023)
Entomopathogenic fungi (EPF) are a class of fungi that are pathogenic to insects and they play an essential role as biocontrol agents for agricultural pests. The presence of indigenous EPFs from recreational forests in the Kinta Region, Perak has not been documented. The aim of this study is to bioprospect indigenous EPF from recreational forests in the Kinta region, Perak and to evaluate the pathogenicity of the indigenous EPF isolates. EPF were isolated from three recreational forests in the Kinta region using Tenebrio molitor as the insect bait. The isolated EPF were characterized based on morphological characteristics and molecular identification. The morphological keys of each isolate were verified with published taxonomic keys by Humber (2012), Samson (1988) and other publications. A total of 7 fungal isolates were obtained from this study. Isolate SK1(a)I1 and SK3(a)I1 were identified as Metarhizium anisopliae. The conidia of M. anisopliae are long and cylindrical shaped, central slight narrowing forming a very long and laterally adherent chain with the length ≤ 9 µm long. The conidial size for both isolates were 6.10 ± 0.67 × 2.24 ± 0.38 µm (SK1(a)I1) and 5.67 ± 0.54 × 2.10 ± 0.21 µm (SK3(a)I1). Other isolates were identified as Clonostachys rogersoniana and Trichoderma spirale and iii Trichoderma virens. PCR was performed to identify the isolates and edited sequences were subjected to BLAST homology search. Molecular characterization revealed that the 7 isolates were M. anisopliae, C. rogersoniana, T. spirale, and T. virens. The pathogenicity of both Metarhizium isolates were evaluated and the mortality rate of T. molitor was 100% and 83.33% after 14 days of inoculation, while other isolates showed no mortality from pathogenicity evaluation. In short, different genera of EPFs were identified and characterized from recreational forests in Perak. However, further study of the pathogenicity of C. rogersoniana should be evaluated. The presence of EPF of recreational forests from other regions in Perak are required to be investigated in the future.